Higher immunoglobulin production in conjugated linoleic acid-supplemented rats during gestation and suckling (2009)
Conjugated linoleic acid (CLA) has been reported to exert beneficial physiological effects on body composition and the immune system. However, little information is available on the influence of CLA on immune function during early life periods. The present study evaluates the effect of feeding an 80:20 mixture of cis-9, trans-11- and trans-10, cis-12-CLA isomers during gestation and suckling on the systemic immune response of weaned Wistar rats. Pups received dietary CLA from dams through the placental barrier and during suckling by breast milk (group A) or by oral administration (group B). Pups from group C only received CLA during suckling by oral administration. Group D constituted the reference group. Milk from dams fed the CLA diet had a high content of CLA and higher IgA and IgG concentrations than rats fed the standard diet. The plasma of pups from groups A, B and C showed six, twelve and nine times higher content of the cis-9, trans-11-CLA isomer than that of the group D pups. Rats from group A exhibited higher serum IgG concentrations than rats from the rest of the groups (22·14 (sem 2·14) v. about 5 mg/ml; P < 0·05), whereas rats from groups A and B showed approximately 2-fold higher splenocyte IgM production than rats from groups C and D. However, CLA supplementation did not influence significantly the splenocyte proliferative response or cytokine secretion. Supplementation during gestation and suckling with an 80:20 cis-9, trans-11–trans-10, cis-12 CLA mix enhances the production of the main in vivo and in vitro Ig isotypes in Wistar rats.